The Effect Of Teacher Teaching Creativity And Learning Media In Improving Student Learning Motivation Of Class X (SMA IT) At Al-Kautsar Ranggo Islamic Boarding School - Atika Atika; Mukhlisin Mukhlisin (JUPE : Jurnal Pendidikan Mandala, 2026)
In the world of education, especially in terms of teaching, teachers play an important role considering that the world of education is increasingly dynamic by facing students who have different understanding backgrounds and varied learning methods, therefore teachers must always be creative in providing teaching and be able to create good learning media, at Pondok Al-Kautsar the teachers always try to prepare learning with the right media. The research approach used is quantitative with survey methods and multiple linear regression techniques. The population in this study were students of this research sample of 30 class X SMA IT AL-Kautsar Ranggo. The results of the study using statistical calculations using SPSS 22 showed that there was an influence between Teacher Teaching Creativity (X1) and Learning Media (X2) in increasing Student Learning Motivation (Y) at SMA IT AL-Kautsar Ranggo. With a significance value of 0.341 <0.05. The results of the coefficient of derivation X1 against Y had an effect of 82.36% and X2 against Y had an effect of 64.51%. The results of the regression equation calculation Y = 72.85 + 0.287X1 + 0.254X2 mean that there is a significant influence between Teacher Teaching Creativity, Learning Media with Student Learning Motivation at SMA IT AL-Kautsar Ranggo. The results of the t test of the Teacher Teaching Creativity variable (X1) on the Student Learning Motivation variable (Y) obtained t count = 2.307> t table = 0.254, this means that Ho is rejected at a significance level of α = 0.05, this means that it is very significant. While the results of the t test of the Learning Media variable (X2) on Student Learning Motivation (Y) obtained t count = 2.765> t table = 0.254, this means that Ho is rejected at a significance level of α = 0.05, this means that it is very significant. The coefficient value of determination of X1 and X2 on Y is 91.8%. Student learning motivation is influenced by teacher teaching creativity and learning media, and the remaining 8.2% is influenced by other factors..